Indigenous practices for management of epilepsy by traditional healers in South Africa - Q. Chabangu; M. S. Maputle; R. T. Lebese; L. Makhado (Эпилепсия и пароксизмальные состояния)
Objective: to determine the indigenous practices that are used to manage epilepsy in South Africa rural communities.Material and methods. A qualitative, ethnographic technique that was exploratory and descriptive was used. Purposive and snowball sampling were used to select a group of 17 traditional healers for in-depth interviews at their homes. The data were analysed through the open coding data analysis method.Results. The traditional healers had different perspectives on the origins and treatment plans of epilepsy based on their knowledge of the disease and their training. They used plants and alternative measures, even though western medicine was still used. The traditional healers’ status in rural communities was acceptable and their treatment modalities were preferred.Conclusion. Traditional healers and primary health care providers must work collaboratively to educate communities on the importance of integrating biomedicine and indigenous practices, as traditional healers had strong inspirations from the communities.